Transnational Archipelago : Perspectives on Cape Verdean Migration and Diaspora. - Batalha, Luís, 1962- (Amsterdam University Press, 2009)
A study of international migration and transnationalism. It explores the Cape Verdean diaspora through its geographical diversity and with a range of thematic perspectives.